1999
DOI: 10.1002/(sici)1097-0215(19990820)84:4<396::aid-ijc11>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum levels of transforming growth factor β1 in Epstein‐Barr virus‐associated nasopharyngeal carcinoma patients

Abstract: Nasopharyngeal carcinomas (NPCs) of non‐keratinizing type are strongly associated with Epstein‐Barr virus (EBV). EBV and its gene products induce the synthesis and/or release of transforming growth factor β1 (TGF‐β1) from human cells and platelets. TGF‐β1 is an immunosuppressive cytokine, and many tumors are known to secrete it, to counter the host immune response. To determine the potential role of this cytokine in the pathogenesis of NPC, 53 serum samples from patients with EBV‐associated NPC and 20 from hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
36
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…10,40 IL12-transduced CTL may also be of interest for other infections, such as HIV, in which the progressive loss of Th1 cytokine production is thought to play a major role in the development of the immunodeficiency syndrome. 41 …”
Section: Discussionmentioning
confidence: 99%
“…10,40 IL12-transduced CTL may also be of interest for other infections, such as HIV, in which the progressive loss of Th1 cytokine production is thought to play a major role in the development of the immunodeficiency syndrome. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were obtained from healthy EBV-seropositive and -seronegative volunteers and from patients suffering from EBV-induced IM, CEI, BL, and NPC. The criteria for the diagnosis of these patients have been detailed in our recent publications (24,25). The CEI patients in this study had prolonged severe relapsing courses of IM with high titers of antivirus capsid antigen and EBV early antigen antibodies in serum and little or no antibody to the EBV nuclear antigens.…”
mentioning
confidence: 99%
“…Recently, we reported that the levels of TGF-␤ are significantly increased in the sera of patients with EBV-associated, undifferentiated, and poorly differentiated nasopharyngeal carcinoma (NPC) (25). EBV is a ubiquitously occurring human gamma herpesvirus and has been etiologically associated with several disease conditions, including different malignancies and lymphoproliferative disorders (reviewed in reference 20).…”
mentioning
confidence: 99%
See 2 more Smart Citations